Karakterisasi Morfologis dan Molekuler Varietas Kedelai (Glycine max) untuk Identifikasi Bahan Baku Obat Tradisional Indonesia - Wiradjaja, Fuad Soegibudiono; Yunita, Oeke (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
Many nutrients and active medicinal compounds in soybean (Glycine max) reduce the risk of cancer, cardiovascular disease, postmenopausal issues, diabetes, and some neurodegenerative disorders. Soybean protein causes several allergic reactions, which necessitates quality control for traditional medicines and herbal products. Morphological and molecular characterization using Random Amplified Polymorphic DNA (RAPD) method were used to control soybean quality. Morphological characterization of 35 soybean varieties from the Research Institute for Various Beans and Tubers (BALITKABI), Malang, East Java, included photos of each variety and seed size, color, hilum color, weight, and special characteristics. RAPD with OPF-3 and OPF-16 primers characterized 35 soybean seed varieties. This study found that morphological characteristics like seed color, hilum color, seed shape, and seed weight are difficult to use to distinguish between varieties, especially if there are no specific features that predominate in these varieties. However, molecular authentication with RAPD can distinguish 35 soybean varieties by the presence of specific polymorphic bands that can only be found in certain varieties.